Estudo da Variabilidade Genética em Populações de Aedes albopictus (Diptera: Culicidae) no Estado do Amazonas, por meio de RAPD-PCR - Cáuper, Fábio Raphael Moreira (2007)
It has been used the RAPD/PCR technics to analysis the genetic Variability in Aedes albopictus, from Cidade Nova, Colina do Aleixo and Compensa neighborhoods of the city of Manaus and Tabatinga municipality in Amazonas state. The results of the RAPD profile analysis revealed 86 bands (locos) in the four populations with variations between 320 and 2.100 pb. Among the four analized populations, the n from Tabatinga has showed greater genetic variability. Even though by the polymorphic locus percentage (P = 100,00) or by its heterozigosity (Ho = 0,3929; He = 0,3981). The smallest genetic variability was detected at the Compensa population (P = 91,83; Ho = 0,3122). Of the three Manaus populations the one from Cidade Nova has shown the greatest genetic variability (P = 97,95; Ho = 0,3662) The q-square test for population differentiation has been significative (2= 466,7269; GL= 98; P < 0,000). The genetic structure was tested being its average value of Fst = 0,0662 ± 0,0096, showing a low genetic structure. Even though, this result has shown that genetic flux is happening among populations and the crossing is much probably aleatory. The values of genetic distances were very low (D= 0,0156 – 0,0786), showing that, populations are genetically very close, being Tabatinga and Compensa, the shortest genetic distance was detected among Cidade Nova and Colina do Aleixo populations (0,0786). The high polymorphism observed on the four analyzed populations cold be a suspicion of a greater genetic plasticity, occurring from its own genetic structure as an adaptable strategy to the Amazonian environment.